2016
DOI: 10.1186/s12931-016-0403-y
|View full text |Cite
|
Sign up to set email alerts
|

Airway smooth muscle NOX4 is upregulated and modulates ROS generation in COPD

Abstract: The burden of oxidative stress is increased in chronic obstructive pulmonary disease (COPD). However, whether the intra-cellular mechanisms controlling the oxidant/anti-oxidant balance in structural airway cells such as airway smooth muscle in COPD is altered is unclear. We sought to determine whether the expression of the NADPH oxidase (NOX)-4 is increased in airway smooth muscle in COPD both in vivo and primary cells in vitro and its role in hydrogen peroxide-induced reactive oxygen species generation. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 12 publications
0
32
0
Order By: Relevance
“…The upregulation of NOX isoforms and resulting progressive increases in ROS generation in asthma, COPD, and other inflammatory pulmonary conditions produce a highly oxidative state 2,4 . Additionally, our laboratory as well as others, have shown that agonism of the β2AR elicits ROS generation 5,6,[8][9][10][11][12]50,51 , and together, these data suggest that chronic use of β2AR agonists in these pulmonary diseases can lead to a significantly higher oxidative load.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The upregulation of NOX isoforms and resulting progressive increases in ROS generation in asthma, COPD, and other inflammatory pulmonary conditions produce a highly oxidative state 2,4 . Additionally, our laboratory as well as others, have shown that agonism of the β2AR elicits ROS generation 5,6,[8][9][10][11][12]50,51 , and together, these data suggest that chronic use of β2AR agonists in these pulmonary diseases can lead to a significantly higher oxidative load.…”
Section: Discussionmentioning
confidence: 99%
“…Inhaled β2-adrenergic receptor (β2AR) agonists are efficacious bronchodilators that are used clinically in patients with pulmonary disorders such as asthma or chronic obstructive pulmonary disease (COPD), the hypercontractility of which is linked to pulmonary inflammation and a highly oxidative environment. In these disease states, the pulmonary epithelia and underlying smooth muscle contain elevated concentrations of reactive oxygen species (ROS), and the membrane-bound ROS generating enzyme NADPH oxidase (NOX) is known to be upregulated [1][2][3] . Of note, NOX4 is overexpressed in the lungs of asthmatic patients compared to healthy controls, while NOX2, NOX4 and the related DUOX2 oxidases are upregulated in airway epithelia of COPD patients, increasing the total burden of oxidative stress in both diseases 2,4 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…An increasing number of researches have revealed that an increased expression of NOX4 was observed in pulmonary diseases 2831. Recently, Hollins et al found that the expression of NOX4 was increased in ASM in COPD both in vivo and in primary cells in vitro 32. Liu et al also showed NOX4 protein was increased in the ASM, and its expression correlated positively with disease severity and inversely correlated with the pulmonary functions in COPD patients 33.…”
Section: Introductionmentioning
confidence: 99%
“…during oxidative phosphorylation [6,7]. NOX4 was the rst kidney-speci c NOX to be discovered, and has since been detected in nerve cells and vascular smooth muscle cells, and in organelles including mitochondria, nuclei and endoplasmic reticulum.…”
Section: Introductionmentioning
confidence: 99%